SYNERGYSTIC EFFECTS OF WOLLASTONITE AND KAOLIN CLAY REINFORCED INTUMESCENT FIRE RETARDANT COATING FOR WOOD PROTECTION - Ku Aizuddin, Ku Muhammad Azeem (2018)
Intumescent Fire Retardant (IFR) coating has been in the industries for quite a long while for its enhancement under thermal performance protection for substrates used in systems like pipelines and building materials. The IFR coating consists of basic ‘active’ ingredients which have become the standards for any research regarding IFR coating system. In the meantime, materials such as Kaolin Clay and Wollastonite has been in research for some years in objective for these materials can enhance properties for the IFR coating. This Final Year Project focus on the studies of the synergistic effects of Wollastonite and Kaolin Clay reinforced intumescent fire-retardant coating for wood protection. A few formulations of IFR coating were prepared with and without the presents of wollastonite and kaolin clay. The substrates were coated with the IFR coatings and cured for 24 hours. The test samples were tested for their char expansion and the percentage differences of average temperature of the IFR coating formulations was calculated.